2014
DOI: 10.1371/journal.pone.0098029
|View full text |Cite
|
Sign up to set email alerts
|

A New Phylogeographic Pattern of Endemic Bufo bankorensis in Taiwan Island Is Attributed to the Genetic Variation of Populations

Abstract: AimTo comprehend the phylogeographic patterns of genetic variation in anurans at Taiwan Island, this study attempted to examine (1) the existence of various geological barriers (Central Mountain Ranges, CMRs); and (2) the genetic variation of Bufo bankorensis using mtDNA sequences among populations located in different regions of Taiwan, characterized by different climates and existing under extreme conditions when compared available sequences of related species B. gargarizans of mainland China.Methodology/Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 82 publications
3
26
0
Order By: Relevance
“…This central mountain range has acted as a barrier for most of the 25 plant and animal taxa studied in Taiwan-wide phylogeographic evaluations (e.g. Toda et al, 1998;Wang, Hsu & Chiang, 2000;Huang, Hwang & Lin, 2002;Cheng, Hwang & Lin, 2005;Oshida et al, 2006;Wu et al, 2006aWu et al, , 2007Jang-Liaw, Lee & Chou, 2008;Kuo et al, 2014;Yu, Lin & Weng, 2014).…”
Section: Discussion Morphological Definition Of Varietiesmentioning
confidence: 99%
“…This central mountain range has acted as a barrier for most of the 25 plant and animal taxa studied in Taiwan-wide phylogeographic evaluations (e.g. Toda et al, 1998;Wang, Hsu & Chiang, 2000;Huang, Hwang & Lin, 2002;Cheng, Hwang & Lin, 2005;Oshida et al, 2006;Wu et al, 2006aWu et al, , 2007Jang-Liaw, Lee & Chou, 2008;Kuo et al, 2014;Yu, Lin & Weng, 2014).…”
Section: Discussion Morphological Definition Of Varietiesmentioning
confidence: 99%
“…plants, ground beetles, and stag beetles [ 12 , 81 – 84 ]. The CMR is another major geographic barrier for genetic differentiation of extant organisms in populations of plants, fishes, frogs, toads, bats, crabs, and stag beetles [ 12 , 35 , 37 , 85 88 ], subspecies of damselflies [ 34 ], and species of snails, fishes, tree frogs, lizards, crabs, crickets, and carabids [ 56 , 83 , 84 , 89 – 94 ]. Hypotheses regarding the evolutionary history, under the hindrance of CMR and periodical glaciations during Pleistocene, for the montane stag beetles exhibiting morphological variations in this study were proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Xueshan Range, Yushan Range, and Alishan Range. These mountain ranges have also been suggested as an important vicariant barrier for the speciation and population differentiation of many organisms, such as fishes, salamanders, toads, crabs, damselflies, and stag beetles during glaciations [ 12 , 28 , 31 – 37 ]. The most interesting case relates to the recognition of two geographic subspecies for some endemic insects, such as butterflies, dragonflies, damselflies, and stag beetles on this island [ 12 , 34 , 38 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Lanyang River was a biogeographic barrier for a high elevation mammal, Formosan wood mouse Apodemos semotus ( Hsu et al 2001 ). Some researchers identified the Xueshan Mountain Range, located in the northern area of Lanyang River, as a biogeographic barrier for lowland animals ( Lin et al 2012 , Shih et al 2011 , Yu et al 2014 ). To our knowledge, this is the first study revealed that the Lanyang River as a barrier for lowland terrestrial animals.…”
Section: Resultsmentioning
confidence: 99%
“…This collision uplifted the Central Mountain Range (CMR), forming a major physical barrier for animals inhabit lowland areas. The CMR has contributed to evolutionary divergences between organisms on either side of the CMR both on interspecific and intraspecific levels ( Huang and Lin 2010 , Jang-Liaw et al 2008 , Kuo et al 2014 , Lin et al 2012 , Wang et al 2007 , Yu et al 2014 ). Aegista subchinensis (Möllendorff, 1884) is one of the most widely distributed species of the genus Aegista in Taiwan and is commonly found in lowland hardwood forests near the CMR ( Hsieh 2003 , Hsieh et al 2006 , Hsieh et al 2013 , Lee and Chen 2003 , Lee and Wu 2004 ).…”
Section: Introductionmentioning
confidence: 99%